Ethylene treatment promotes umami taste-active amino acids accumulation of Torreya grandis nuts post-harvest by comparative chemical and transcript analyses. (15th May 2023) - Zhang, Zuying; Chen, Wenchao; Tao, Liu; Wei, Xixing; Gao, Lingling; Gao, Yadi; Suo, Jinwei; Yu, Weiwu; Hu, Yuanyuan; Yang, Baoru; Jiang, Huifeng; Farag, Mohamed A.; et al.
Highlights: The composition of amino acids is important for Torreya grandis nuts quality. Ethylene induced amino acid contents in Torreya grandis nuts after harvest. PCA revealed that umami amino acids were distinctly separated with ethylene treatment. KEGG analysis indicated that alanine aspartate and glutamate metabolism were enriched. RT-qPCR confirmed that ethylene regulated gene expression of Glu and Asp metabolism. Abstract: Amino acids play critical roles in physiological processes and also contribute significantly to fruit quality. In this study, the effect of exogenous ethylene on amino acids metabolism and related genes expression in Torreya grandis were investigated. The results revealed that ethylene treatment (3000 μL L -1 for 24 h) significantly increased amino acids level. Umami amino acids were distinctly upregulated in ethylene-treated versus control nuts, with glutamic and aspartic acids to demonstrate 1.9-fold and 2.1-fold increase. Transcriptome analysis revealed that deferentially expressed genes were mainly enriched in alanine aspartate and glutamate metabolism. RT-qPCR confirmed that ethylene treatment up-regulated expression of their biosynthesis genes ( TgGOGAT1, TgAATC1, TgAATC4 ) concurrent with suppression of their degradation enzymes ( TgGS2, TgGAD1, TgGAD3, TgASNS1 ). Ethylene treatment appears to promote umami taste-active amino acids and improve T. grandis nut quality post-harvest.